2016
DOI: 10.1016/j.kjms.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Salvage urethroplasty using skin grafts for previously failed long‐segment urethral strictures

Abstract: The aim of this study was to describe a technique using full-thickness skin grafts (FTSGs) from different parts of the body for salvage urethroplasties and the present outcomes. A total of 24 men underwent urethroplasties for strictures averaging 7.7 cm (range, 5-17 cm) in length, using FTSGs from the inner arm, inner thigh, or abdominal skin. Each of these cases had at least one failed urethroplasty. Twenty-four patients underwent surgery for 26 urethral strictures, with a mean follow-up period of 23.2 (5-44)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Different graft sources provided success rates of 80% for skin grafts from the arm, 60% inner thigh skin graft, 50% for abdominal skin graft as reported by one study by Sevinc et al [32] and 60% for scrotal skin graft reported by Andrich et al [29].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Different graft sources provided success rates of 80% for skin grafts from the arm, 60% inner thigh skin graft, 50% for abdominal skin graft as reported by one study by Sevinc et al [32] and 60% for scrotal skin graft reported by Andrich et al [29].…”
Section: Resultsmentioning
confidence: 92%
“…Three studies reporting anterior strictures focused on hypospadias cases with 5 studies not discussing the location of the urethroplasty. The mean length of the stricture was reported in six studies with the mean length reported between 4 and 8 cm [3234, 39, 41, 43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ureteroscopy is performed at months 1, 3, 6, and 12 after the removal of the catheters. At each follow-up visit, complete urine examination, uroflowmetry, and postmicturition residual volume measurementshould be performed (51,52).…”
mentioning
confidence: 99%